Bleomycin-Induced Flagellate Erythema in a Patient Diagnosed with Ovarian Yolk Sac Tumor - Stergios Boussios; Michele Moschetta; Jennifer McLachlan; Susana Banerjee (Case Reports in Oncological Medicine)
Flagellate linear hyperpigmentation can rarely be caused by the chemotherapy agent, bleomycin. Herein, we describe the case of a 20-year-old woman treated with bleomycin for an ovarian yolk sac tumor and review the prominent features of this form of dermatitis.